Evaluation of a nanocomposite based on reduced graphene oxide and gold nanoparticles as an electrochemical platform for detection of sulfamethazine - Silva, Martin [UNESP] (2019)
A nanocomposite based on reduced graphene oxide (rGO) and gold nanoparticles (AuNPs) was synthesized by the microwave-assisted hydrothermal method and applied in the determination of sulfamethazine (SMZ) in swine effluent using a glassy carbon (GC) electrode. The rGO-AuNPs nanocomposite was characterized morphologically, electrochemically and spectrochemically, showing that rGO was modified with the AuNPs. The GC/rGO-AuNPs electrode was optimized for the determination of SMZ, achieving detection limits of 0.1 µmol L−1 . The proposed sensor was successfully applied to the determination of SMZ in synthetic swine effluent samples.